الذكاء الاصطناعي في خدمة علم الحديث: المجالات والتحديات والمخاطر: Artificial Intelligence in the Service of Hadith Sciences: Opportunities, Challenges, and Risks - Assad, Muhammad; Bayanouni, Fathuddin (Al-Irfan, 2025)
The science of Hadith is one of the most prominent branches of Islamic jurisprudence, representing the primary means of understanding the Sunnah of the Prophet Muhammad (peace and blessings be upon him), which is the second source of Islamic law after the Holy Quran. Scholars have exerted tremendous efforts in collecting, documenting, verifying, and classifying Hadiths from the earliest times to the present day. With the significant advancements in artificial intelligence (AI), the possibility of employing this modern technology in the service of Hadith studies has emerged. Several questions arise regarding this technology: Can AI replace human intellect in verifying Hadiths? What are the limits of its use? Are there any potential legal or academic risks associated with its application in this field? This research aims to explore the areas of AI application in the service of Hadith studies, review its applications in this field, and highlight the most significant challenges and risks it faces. Among the findings of this research is the potential for utilizing AI techniques in five key areas: Hadith verification, evaluation of Hadiths, study of the chain of transmission (isnad), explanation of the text (matn) of Hadiths, and thematic studies of Hadiths. The use of these technologies faces several challenges, including reliance on input data, a lack of accurate data, a lack of contextual awareness, and weak critical thinking. It is also fraught with risks, most notably the issuance of hadith rulings by unqualified individuals and the blurring of lines between technical and legal standards. Artificial intelligence can be a powerful tool in the field of hadith studies, provided there is specialized scholarly oversight that adheres to the rigorous methodological principles of this noble discipline.